ORTHODONTIC TREATMENT NEEDS AND ASSOCIATION BETWEEN MALOCCLUSION AND ORAL HYGIENE BEHAVIORS - Al-Qurashi, Hatim; Al-Farea, Majed; Alshamrani, Husam Abdulrahman; Almasoud, Naif N; Nazir, Muhammad Ashraf (Pakistan Oral & Dental Journal, 2018)
The objective of the study was to determine orthodontic treatment needs and investigate the relationship between malocclusion and oral hygiene behaviors and oral problems among male Saudi schoolchildren in Dammam. This cross-sectional study involved male intermediate schoolchildren (age 12-16 years) from public schools of Dammam, Saudi Arabia. A sample of 376 children was selected using multistage random sampling. The orthodontic treatment needs were assessed using dental aesthetic index (DAI).The World Health Organization (WHO) questionnaire was used to collect data about oral hygiene habits and problems. The prevalence of malocclusion was 19.7%. Thirty four (9%) children had DAI scores (26-30), and had definite malocclusion that required elective treatment. Twenty two (5.9%) children had severe malocclusion ( DAI scores 31-35), and treatment was highly desirable. DAI score of ? 36 was found in 18 (4.8%) children with severe or handicapping malocclusion that required mandatory orthodontic treatment. A higher proportion of children (85.1%) with malocclusion cleaned their teeth daily in comparison with children without malocclusion (76.8%). A significantly (p = 0.023) higher proportion of students with malocclusion (60.8%) was dissatisfied with their dental appearance than those with normal occlusion (46%). In conclusion, a high prevalence of malocclusion was observed among male schoolchildren in Dammam. The study found no statistically significant relationship between malocclusion and oral hygiene behaviors.
Keywords: Malocclusion; orthodontic treatment needs; oral hygiene behaviors